VD_FINDINFO Jug / 2013 / 143 vom 7. März 2013 - VD Tribunal cantonal (2013)
INDICE, LIBRE APPRÉCIATION DES PREUVES | 10 CP, 90 ch. 2 LCR, 91 al. 1 LCR, 94 ch. 1 LCR, 95 ch. 2 LCR, 19 ch. 1 al. 6 LStup, 19 ch. 2 let. a LStup